DEGRADASI SENYAWA PARAQUAT DALAM PESTISIDA GRAMOXONE® SECARA FOTOLISIS DENGAN PENAMBAHAN TiO2-ANATASE - Yuni Era; Safni -; Hamzar Suyani (Jurnal Riset Kimia, 2008)
ABSTRACT This research is conducted to know whether the photolysis method by adding TiO2-anatase can degrade the paraquat compound in Gramoxone pesticide. Photolysis method is conducted by using UV 10 watt lamp at the wavelength of 365 nm. The result shows that photolysis method could degrade the paraquat compound at 4.0 mg/L concentration as 16.02% after 60 minutes irradiation. Paraquat compound with the similar concentration by adding 10 mg unmixed TiO2-anatase could degrade 26.01% after 60 minutes irradiation and 62.30% by mixing TiO2-anatase. Furthermore, paraquat with the same concentration and TiO2-anatase addition could degrade 99.54% after 240 minutes irradiation. Keywords : degradation, photolysis, paraquat, anatase-TiO2